Crocetin Overproduction in Engineered Saccharomyces cerevisiae via Tuning Key Enzymes Coupled With Precursor Engineering - Song, Tianqing; Wu, Nan; Wang, Chen; Wang, Ying; Chai, Fenghua; Ding, Mingzhu; Li, Xia; Yao, Mingdong; Xiao, Wenhai; Yuan, Yingjin (Frontiers in Bioengineering and Biotechnology, 2020)
Crocetin, an important natural carotenoid dicarboxylic acid with high pharmaceutical values, has been successfully generated from glucose by engineered Saccharomyces cerevisiae in our previous study. Here, a systematic optimization was executed for crocetin overproduction in yeast. The effects of precursor enhancement on crocetin production were investigated by blocking the genes involved in glyoxylate cycle (CIT2 and MLS1). Crocetin titer was promoted by 50% by △CIT2 compared to that of the starting strain. Then, the crocetin production was further increased by 44% through introducing the forward fusion enzymes of PsCrtZ (CrtZ from Pantoea stewartii)-CsCCD2 (CCD2 from Crocus sativus). Consequently, the crocetin titer reached to 1.95±0.23 mg/L by overexpression of PsCrtZ-CsCCD2 followed by medium optimization. Eventually, a titer of 12.43±0.62 mg/L crocetin was achieved in 5-L bioreactor, which is the highest crocetin titer reported in micro-organisms.